2011
DOI: 10.1007/s10562-011-0664-5
|View full text |Cite
|
Sign up to set email alerts
|

Perovskite-Based Lean-Burn NO x Trap Catalysts Without Using Platinum Group Metals: K/LaCoO3/Ce1−x Zr x O2

Abstract: A series of Ce 1-x Zr x O 2 (x = 0, 0.1, 0.2, 0.3) solid solution supported lean-burn NO x trap (LNT) catalysts K/LaCoO 3 /Ce 1-x Zr x O 2 were prepared by successive impregnation. After sulfation the supported perovsikte LaCoO 3 was well maintained; reducing treatment partly destroyed the perovsikte, but it can be well recovered by re-oxidation treatment. Based on NO x storage and sulfurresisting performance of the catalysts, the optimal atomic ratio of Zr in Ce 1-x Zr x O 2 support is x = 0.2. The catalyst K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…The preparation of the CeZrO 2 /γ-Al 2 O 3 catalyst support was done by a citrate complexation incipient wetness impregnation method, details of which can be found in our earlier publication . Thereafter, 0.92 wt % palladium was then added to the support CeZrO 2 /γ-Al 2 O 3 using the incipient wetness impregnation method.…”
Section: Methodsmentioning
confidence: 99%
“…The preparation of the CeZrO 2 /γ-Al 2 O 3 catalyst support was done by a citrate complexation incipient wetness impregnation method, details of which can be found in our earlier publication . Thereafter, 0.92 wt % palladium was then added to the support CeZrO 2 /γ-Al 2 O 3 using the incipient wetness impregnation method.…”
Section: Methodsmentioning
confidence: 99%
“…The acid-to-metal-cation ratio was 2.1:1 to enable the total complexation of all metal ions. 21 The resulting solution was continuously stirred at 75 °C until obtaining a colorless gel and subsequently stirred overnight at room temperature. The concentrated solution was then impregnated on γ-Al 2 O 3 (Sasol, Puralox SBa200, Brunsbuẗtel, Germany) at a ratio of 20/80 wt % CeZr/Al 2 O 3 .…”
Section: Methodsmentioning
confidence: 99%
“…The support was prepared through a citrate complexation incipient wetness impregnation procedure. This method consisted in dissolving Ce­(NO 3 ) 2 (Alfa Aesar, Haverhill, Massachusetts, United States) and Zr­(NO 3 ) 2 (Sigma-Aldrich, St. Louis, Missouri) precursors in a deionized water solution of citric acid (VWR International AB, Gothenburg, Sweden) at a ratio of 35/65 wt % Ce/Zr. The acid-to-metal-cation ratio was 2.1:1 to enable the total complexation of all metal ions . The resulting solution was continuously stirred at 75 °C until obtaining a colorless gel and subsequently stirred overnight at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Compared with the single oxide CeO 2 , the binary CeO 2 –ZrO 2 or ternary Y 2 O 3 –CeO 2 –ZrO 2 solid solution usually has larger specific surface area, more oxygen vacancies and higher oxygen storage capacity (OSC), so, in this work, these solid solutions were prepared and used as supports of LNT catalysts. As to the NOx storage component, many works have demonstrated that potassium is an appropriate NOx storage material since it has strong basicity and better regeneration performance after sulfur poison as compared with barium. …”
Section: Introductionmentioning
confidence: 99%
“…Such unconspicuous shifts suggest the formation of small amounts of CeZrO or YCeZrO solid solutions by referring to Ce x Zr 1-x O 2 system 28. In addition to the supports, the perovskite LaCoO 3…”
mentioning
confidence: 99%